Pseudo-Winging of the Scapula Caused by Scapular Osteochondroma: Review of Literature and Case Report. (June 2015) - Flugstad, Nicholas A.; Sanger, James R.; Hackbarth, Donald A.
Abstract A 20-year-old male was evaluated for winging of the scapula and an enlarging axillary mass of 4 months' duration. Imaging demonstrated a multiloculated cystic lesion that extended into the axilla and superiorly displaced the brachial plexus and axillary vessels surrounding an exostotic mass arising from the scapula. Surgery confirmed the mass to be a benign osteochondroma with a reactive bursa. The long thoracic nerve was intact and the serratus anterior muscle contracted normally with nerve stimulation. The scapular winging resolved completely following resection of the osteochondroma, and shoulder and arm function remained normal. A literature review of causes of pseudo-winging of the scapula was performed. Scapular osteochondroma is a rarely reported cause of scapula winging.